Student stigmatization: Threat to school coexistence - De la Rosa Figueroa, Julissa (GACETA DE PEDAGOGÍA, 2021)
Different human specificities converge in educational institutions that affect interactions and coexistence between students, which causes problems of violence, discrimination and stigmatization that can cause isolation, school dropout, exclusion, among others. The present research aims to analyze the theoretical elements of student stigmatization and its implications in school coexistence. The study has a qualitative approach to documentary design, it was based mainly on the analysis and interpretation of information from electronic and printed sources by means of the hermeneutical method. Among the results obtained, it is found that educators have a great responsibility in the eradication and reduction of student stigmatization, since sometimes they go unnoticed or are consciously or unconsciously promoted not only by the students themselves, but also by the institutional authorities, teachers and context. Therefore, the challenge is to build necessary mechanisms from school institutions from which respect for difference and for others are fostered and strengthened.